Incorporation of tritium by pepper and eggplant cultures with short-term exposure to tritium oxide - E. N. Polivkina; E. S. Sysoyeva; E. V. Romanenko; L. F. Subbotina; A. V. Panitskiy; F. F. Zhamaldinov; L. B. Kenzhina (Радиационная гигиена)
The article presents results of a study of tritium incorporation by vegetable crops with short-term aerial exposure to tritium oxide in laboratory and field conditions. Plants are a key link in the process of tritium migration both in the ecosystem as a whole and in the trophic structure in particular. As a result of photosynthesis, much of tritium is incorporated into the organic matter of plants. In this aspect, the study of tritium incorporation processes and its possible contribution to human radiation exposure from ingested crop products is a relevant task. The aim of the study was to assess tritium incorporation by vegetable crops quantitatively at aerial entry of the radionuclide in the form of tritium oxide. To achieve this goal, laboratory (in the chamber) and field (in the territory of the former Semipalatinsk Test Site) experiments were conducted with commonly cultivated pepper (Capsicum annuum) and eggplant (Solanum melongena) that were affected by short-term exposure to tritium oxide vapors. Air was sampled with a tritium collector “OS 1700”. Plant samples for measuring organically bound tritium were prepared using a “Sample Oxidizer” unit. Tritium activity in samples was measured with “QUANTULUS 1220”. It was found that tissue free water tritium activity in leaves of Capsicum annuum and Solanum melongena was 1-2 orders of magnitude higher than in stems and fruits. The distribution of tissue free water tritium in both crops with a short-term aerial exposure is described by a decreasing series: “leaves < stems < fruits”. The difference between the tissue free water tritium and organically bound tritium concentration in plants for all exposure variants was also 1-2 orders of magnitude. For organically bound tritium, no distinct regularity in the distribution of plant parts was established, which is most likely due to the short period of exposure. By the time the fruits were fully ripe, a significant decrease in the activity of tissue free water tritium (the main source of the formation of organically bound tritium in the post-exposure period) in all plant parts was observed. For organically bound tritium, both an increase and a decrease in the concentration were noted in leaves and stems, and in ripe fruits it remained almost at the same level as at the end of the exposure. The conversion rate of tritium in field conditions was 15-30 times than in the chamber. Organically bound tritium translocation into edible parts of vegetable crops in field conditions was 2-4 times higher than in the chamber, regardless of the tritium oxide concentration in air and leaves. According to a conservative assessment, the possible contribution to the dose of internal exposure from ingested tritium per 1 kg of vegetables contaminated as a result of short–term exposure, based on the absolute activity of radionuclide forms in Capsicum annuum and Solanum melongena fruits will be: for tissue free water tritium – 0.7 and 5.6 nSv; for organically bound tritium – 1.7 and 2.4 nSv, respectively. Since the levels of tritium oxide in the emissions of nuclear fuel cycle enterprises are much lower compared to experimental ones, the possible contribution of tritium to the dose of public internal exposure from the ingestion with crop products after a short-term tritium oxide exposure will be negligible.